A local marine source of atmospheric particles in the High Arctic. (15th September 2022) - Nøjgaard, J.K.; Peker, L.; Pernov, J.B.; Johnson, M.S.; Bossi, R.; Massling, A.; Lange, R.; Nielsen, I.E.; Prevot, A.S.H.; Eriksson, A.C.; Canonaco, F.; Skov, H.
Abstract: The chemical composition of non-refractory submicron aerosol (NR-PM1 ) was characterized at the Villum Research Station (Villum) at Station Nord in North Greenland during spring-summer 2016 using a Time of Flight Aerosol Chemical Speciation Monitor (ToF-ACSM). The composition is dominated by sulfate (48%) and organic species (40%). Positive Matrix Factorization (PMF) identified three key factors corresponding to a primary hydrocarbon-like organic aerosol (HOA), and two types of secondary organic aerosol: oxygenated organic aerosol (OOA) and a marine organic aerosol (MOA). The HOA factor accounts for 5% of the organic aerosol mass, which is consistent with previous findings at Villum. The OOA factor accounts for 77% of the organic aerosol mass and correlates with accumulation mode particles, which supports previous findings indicating that oxidized organic aerosols are predominantly from long-range transport during winter and spring at Villum. The MOA factor was characterized by mass spectral fragments of methane sulfonic acid (MSA) from atmospheric oxidation of dimethyl sulfide, for which reason the MOA factor is considered to be of biogenic origin. MOA accounts for 18% of the organic aerosol mass and correlates with locally produced Aitken mode particles. This indicates that biogenic processes are not only a significant source of aerosols at Villum, but MOA also appears to be formed in the vicinity of the measurement site. This local geographical origin was confirmed through air mass back trajectory modelling and source-receptor analysis. During May, air masses frequently arrived from the east, with source regions for the MOA factor and therewith MSA located in the Barents Sea and Lincoln Sea with lesser contributions from the Greenland Sea. During June, air mass origin shifted to the west, with source regions for the MOA factor and MSA shifting correspondingly to Baffin Bay and the Canadian Arctic Archipelago. While shifting transport patterns between May and June lead to shifting source regions, sea ice likely played a role as well. During May, marginal ice zones were present in the Barents Sea between Svalbard and Franz Josef Land, while during June, sea ice in the northern part of Baffin Bay retreated and sea ice in the Canadian Arctic Archipelago decreased. Although May and June experienced different transport patterns and sea ice conditions, levels of the MOA factor and MSA were similar between the months. This is likely due to similarities between marine biological activities in the Barents Sea and Baffin Bay. This research highlights the complex relationship between transport patterns, sea ice conditions, and atmospheric particle concentrations. Multiyear aerosol chemical composition from several High Arctic sites is encouraged to determine the full effects of ocean-atmosphere interactions and transport patterns on atmospheric aerosol concentrations. Highlights: Factor analysis revealed 3 sources to Arctic aerosols: HOA, OOA and MOA. Marine Organic Aerosols (MOA) accounted for 18% in Spring/Summer Arctic aerosols. MOA correlated with Aitken mode particle mass. The local geographical origin of MOA was confirmed by back trajectories and source-receptor analysis.